Self-monitoring of flexural fatigue damage in large-scale steel-reinforced cementitious composite beams - Çelik, Damla Nur; Yıldırım, Gürkan; Al-Dahawi, Ali; Ulugöl, Hüseyin; Han, Baoguo; Şahmaran, Mustafa (Cement & concrete composites, 2021)
Self-sensing in cementitious materials is a topic of great interest to many. However, to date, the subject has been mainly investigated by using small-scale specimens, which calls the reliability and applicability for real-time structures into question. This study investigates the self-sensing capability of large-scale steel-reinforced cementitious composite beams subjected to different ranges of fatigue loading under four-point bending. Multi-walled carbon nanotubes (CNT) or chopped carbon fibers (CF) were used to improve the electrical properties of the beams. Following the instantaneously-recorded impedance results from previously-embedded brass electrodes in the tensile region of the beams, and after calculating the fractional changes in electrical resistivity (FCER) results, self-sensing was evaluated by using a 2-probe electrical resistivity meter. Results show that the proposed testing configuration is successful in adequately capturing the different ranges of fatigue loading for both CNT- and CF-based beams, regardless of the presence of steel reinforcement. While the FCER results of the CF-based beams are comparably higher than those of the CNT-based beams for almost all ranges of fatigue loading, implying for a better self-sensing capability, the self-sensing plots of CF-based beams are not stable and exhibit abrupt/unexpected changes instantaneously. The self-sensing plots of the CNT-based beams, however, are relatively stable, working correspondingly with the applied loading. They do not exhibit abrupt changes, regardless of the range of fatigue loading, which points out for the better stability of the CNT-based conductive network and is highly desirable for structures frequently subjected to dynamic loads in service such as bridge decks, overlays and pavements. For the given mixture proportions, beam configuration and measurement technique, the use of CNT is therefore suggested for self-sensing of fatigue damage. The authors believe that the findings reported here are valuable since the beams developed for this study can be used as small replicates of larger scale beams used in real-time structures exposed to fatigue loading.